Green Electroluminescence of Al/Tb/Al/SiO2 Devices Fabricated by Electron Beam Evaporation. Issue 3 (18th October 2017) - Frieiro, Juan Luis; Blázquez, Oriol; López‐Vidrier, Julian; López‐Conesa, Lluis; Estradé, Sònia; Peiró, Francesca; Ibáñez, Jordi; Hernández, Sergi; Garrido, Blas
Abstract : In this work, the fabrication and the structural, optical and electrical properties of Al‐Tb/SiO2 nanomultilayers have been studied. The nanomultilayers were deposited by means of electron beam evaporation on top of p‐type Si substrates. Optical characterization shows a narrow and strong emission in the green spectral range, indicating the optical activation of Tb 3+ ions. The electrical characterization revealed conduction limited by the electrode, although trapped‐assisted mechanisms can also contribute to transport. The electroluminescence analysis revealed also emission from Tb 3+ ions, a promising result to include this material in future optoelectronics applications as integrated light‐emitting devices. Abstract : Optoelectronic devices consisting of Al/Tb/Al/SiO2 nanomultilayers, as depicted in the figure, are fabricated by means of electron beam evaporation . Electrical characterization allows identifying a conduction limited by electrode as the governing mechanism in the device. Optical and electro‐optical features indicate the activation and thus green emission of Tb 3+ ions, suggesting the possibility for future applications as integrated light‐emitting devices.